2020
DOI: 10.1177/1708538120905430
|View full text |Cite
|
Sign up to set email alerts
|

Changes and significance of T helper-9 cells and interleukin-9 in patients with atherosclerotic chronic lower limb ischemia: Effect on IL-17 release

Abstract: Objectives Atherosclerosis is considered as a chronic inflammatory disorder where the central role of T cells in its pathogenesis is well known. T helper-9 cells have a distinctive effect upon the inflammatory processes. They stimulate macrophages via secretion of their cytokine interleukin-9. Based on its known involvement with other inflammatory disorders, we hypothesized that interleukin-9 might be associated with the inflammatory limb of peripheral atherosclerotic disease. Methods We tested this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…IL-17 A is a proinflammatory cytokine mainly secreted by Th17 cells [ 24 ]. Additionally, clinical studies have found that peripheral blood mononuclear cells (PBMCs) in atherosclerosis patients release increased IL-17, especially in severe patients [ 25 ]. In atherosclerosis, endothelial dysfunction and vascular inflammation are reversed by lowering IL-21 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 A is a proinflammatory cytokine mainly secreted by Th17 cells [ 24 ]. Additionally, clinical studies have found that peripheral blood mononuclear cells (PBMCs) in atherosclerosis patients release increased IL-17, especially in severe patients [ 25 ]. In atherosclerosis, endothelial dysfunction and vascular inflammation are reversed by lowering IL-21 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%